BEYOND PROMOTION: CULTURAL PARADIPLOMACY AS A STRATEGY FOR BETAWI CULTURAL RESILIENCE IN JAKARTA - Ageu Lagena; Gilang Nur Alam; Windy Dermawan (International Journal of Cultural and Social Science, 2026)
Betawi culture in Jakarta faces accelerating marginalization due to globalization, urbanization, and digital homogenization, threatening its continuity. This study employs a descriptive qualitative approach using document analysis of policy papers, foreign cooperation reports, and digital archives, with content analysis and source triangulation to examine how the Provincial Government of DKI Jakarta employs cultural paradiplomacy to strengthen the resilience of Betawi culture. The findings identify three mutually reinforcing mechanisms: representational that build international visibility and symbolic legitimacy; collaborative that mobilize multi-actor partnerships for community-based preservation; and transformational engagement that embeds cultural protection into urban governance through policy learning and institutional reform. Together, these mechanisms show that cultural paradiplomacy operates not only as city branding but as a multi-layered strategy for protecting vulnerable local heritage, offering lessons for other regions within Indonesia’s centralized foreign policy system.